2018
DOI: 10.1111/trf.15115
|View full text |Cite
|
Sign up to set email alerts
|

The P1 histo‐blood group antigen is present on human red blood cell glycoproteins

Abstract: BACKGROUND The P1 antigen was first described in 1927 and belongs to the P1PK histo‐blood group system, together with Pk and NOR. The A4GALT‐encoded 4‐α‐galactosyltransferase synthesizes these antigens and has been considered to extend glycolipids exclusively. However, contradicting studies have been published regarding the presence of P1 on human glycoproteins. In other species, P1 occurs on glycoproteins. Furthermore, human ABH antigens occur on both glycolipids and glycoproteins and are biochemically relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…P1 antigens on glycoproteins are known to bind STx, and column coupling with P1-containing proteins has been used to purify STx (25,26,33). P1 antigens on glycoproteins are infrequently observed in mammalian cells, although erythrocytes are likely to express them (34). In this study, hA4GalT synthesized a small amount of P1 antigens on glycoproteins only when overexpressed (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…P1 antigens on glycoproteins are known to bind STx, and column coupling with P1-containing proteins has been used to purify STx (25,26,33). P1 antigens on glycoproteins are infrequently observed in mammalian cells, although erythrocytes are likely to express them (34). In this study, hA4GalT synthesized a small amount of P1 antigens on glycoproteins only when overexpressed (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, rs5751348 should be used as the genetic determinant to predict P1 antigen expression 22 . In a recent study, a new P 1 / P 2 ‐allelic discrimination assay based on rs5751348 was validated, and the results were confirmed to be correlated to the P 1 / P 2 status 36 …”
Section: Discussionmentioning
confidence: 96%
“…Since then, there was a general agreement that GSLs are the only carriers of the P1 glycotope. Recently (39), suggested that some human erythrocytes of P 1 phenotype display P1 not just on GSLs, but also on glycoproteins, and implicated GLUT1 and Band 3 as likely major carriers of the P1 glycotope. However, the evidence was limited to western blotting results.…”
Section: Discussionmentioning
confidence: 99%